Aspectos metacognitivos na leitura do indexador - Dulce Amelia de Brito Neves (2004)
Considering indexers reading as a first element in the indexing process, this thesis aims at identifying metacognitive strategies used by such professional during the reading for indexing. It seeked to identify similarities and differences in the use of metacognitive strategies among indexers and a control group composed by proficient readers. It was taken into account strategies of monitored misunderstanding, hypothesis construction, information clues between sentences and paragraphs, question-answering, abstract mental construction, value judgment repetition and evocation. The method used was verbal protocol analysis, a method which allows obtaining individual accounts, exploring individual cognition from a task execution or from task execution remembrances, and which offer qualitative information. Results show indexers read similarly to proficient readers. Differences are perceived only in the frequency indexers use abstract mental constructions and value judging during the reading procedure. It was also tested a methodological question concerned to text, in its marked and non-marked condition. Results show the need for providing a restructuring of librarian formation, searching for methods in which the use of metacognition could be contemplated in the teaching of reading strategies.